Tremor burst and triggering processes in Cascadia after the 2022 Hunga Tonga-Hunga Ha’apai volcanic eruption - Sambit Sahoo; Batakrushna Senapati; Bhaskar Kundu; Yijian Zhou; Abhijit Ghosh; Shuanggen Jin (Geomatics, Natural Hazards & Risk)
Episodic Tremors and Slip (ETS) are highly susceptible and sensitive to external stress perturbations. The tidal and remote triggering phenomena of tremors are well-documented globally, however, the significance of the delayed triggering mechanism remains elusive. In this paper, the possibilities of the tremor modulation by the Lamb waves induced from the Hunga Tonga-Hunga Ha’apai volcanic eruption (SW Pacific) on 15 January 2022 have been explored. The increasing activity of tremors after eruption has been explored at the study region of Cascadia subduction zone where such tremor do not correlate with tidal stress perturbations or remote triggering by far-off or near-by earthquakes. The increasing tremor activities are observed during the propagation of the Lamb wave cycles (L1, L2, L3, L4) and more interestingly during inter-ETS period. From the seismic waveform analysis, we observe two coherent packets of teleseismic energy on 15 January 2022, which corresponds to arrival of surface and Lamb waves, respectively. The delayed triggering of tremors may be linked either with the teleseismic surface waves or Lamb waves from the volcanic explosion, or both. Although we cannot rule out coincidence, the delayed triggering by Lamb waves appears to be consistent with magnitude-dependent time delay and 2-D coupled pore pressure induced diffusion model.